Prevalence of temporomandibular disorders in institutionalized older people - Zenia Masiel Criado Mora; Rosalba Cabrera González; Rolando Saez Carriera; José Montero Parrilla; Ileana Grau León (Editorial Ciencias Médicas, 2014)
Introduction: the Temporomandibular Disorders (TMD) are a series of signs and symptoms of multifactoral etiology in the mouth-face area. In Cuba, there exist several research studies about TMD, mainly in young people with natural dentition, but no extensive references of this kind are known in the older adult. Objective: to identify the prevalence of temporomandibular disorders in the institutionalized older adults in two homes for the elderly located in Havana from March to April 2012. A survey was administered in which sex, age, sign and symptoms data were collected. The evaluated clinical manifestations were muscular pain, difficult opening and closure movement, joint pain, articular and muscular pain, articulary noises, limited mouth opening, limited laterality and propulsion movements, jaw deviation. Methods: a descriptive and cross-sectional study of 113 institutionalized older adults of both sexes was carried out from March to April of 2012 in two homes for elderly in Havana. A survey was administered in which sex, age, sign and symptoms data were collected. The evaluated clinical manifestations were muscular pain, difficult opening and closure movement, articular pain, articular and muscular pain, articular noises, limited mouth opening, limited laterality and propulsion movements, jaw deviation. Results: in the studied older adults, 40.70% were affected in their temporomandibular articulation. The articular noises were the most prevalent sign in all age groups (76.08 %), affecting 82.35 % of men and 72.41 % of women, followed by muscular pain in 52.17 % of those affected, with higher percentage found in women (58.62 %) than in men (41.17 %). Difficulties in opening and closing the mouth were detected in 28.26 % of the affected people, being more prevalent in females (34.48%) than in males (17.14 %). Conclusions: A high prevalence of TMD was observed in the studied older people. The most frequent symptoms and sings by age and sex were articular noises and the muscular pain, and the difficulty in making the opening and closing movements of the mouth. Keywords: temporomandibular disorders, temporomandibular articulation, institutionalized older adult.